2009
DOI: 10.1590/s0100-736x2009000200010
|View full text |Cite
|
Sign up to set email alerts
|

Achados patológicos e imuno-histoquímicos em cães infectados naturalmente pelo vírus da cinomose canina

Abstract: RESUMO.-A cinomose canina é uma doença viral e afeta principalmente os sistemas respiratório, gastrintestinal e nervoso. Neste trabalho foram analisados os achados patológicos e imuno-histoquímicos de 54 cães com cinomose de um total de 760 cães necropsiados no período de julho de 2006 a outubro de 2007. As lesões macroscó-picas observadas foram caracterizadas por corrimento ocular e nasal mucopurulentas, hiperqueratose dos coxins digitais, pulmões avermelhados e não colapsados, atrofia do timo, conteúdo intes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
15

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 25 publications
(30 reference statements)
2
9
0
15
Order By: Relevance
“…However, in some studies, proportionally more males relative to females were infected by CDV. This was observed in Porto Alegre/RS, where male dogs contributed to 59% of the total number of dogs affected (SONNE et al, 2009), and with similar results being described in Madras city, India (ALEX; DHANAPALAN, 1994).…”
Section: Sexual Preference and Age-related Distribution Patternssupporting
confidence: 79%
See 4 more Smart Citations
“…However, in some studies, proportionally more males relative to females were infected by CDV. This was observed in Porto Alegre/RS, where male dogs contributed to 59% of the total number of dogs affected (SONNE et al, 2009), and with similar results being described in Madras city, India (ALEX; DHANAPALAN, 1994).…”
Section: Sexual Preference and Age-related Distribution Patternssupporting
confidence: 79%
“…Further, epidemiological data have demonstrated that mongrels represented the largest populations (54%) of dogs infected with CDV in Santa Maria/RS (HEADLEY; GRAÇA, 2000), contributed to 44% of CDV-induced cases diagnosed in Porto Alegre/RS (SONNE et al, 2009), and 30% of all dogs with CDV from Belém/PA (GUEDES et al, 2010). Elevated indices of CDV infections in Brazilian mongrels are directly related to their lifestyle.…”
Section: The Importance Of Mongrel Dogsmentioning
confidence: 99%
See 3 more Smart Citations